Rotina no trabalho: motivação e conformismo - Oliveira, Marina Slade (1976)
This study has been designed in order to assess a) Motivation level, based on Maslow and Herzberg concepts, and b) Conformity and tencency to order and meticulous-ness, as defined by Comrey in two groups composed of individuals doing routine work and individuals doing non-routine work, respectively. It has been our purpose to prove that the individuals doing routine work tend to be motivated in a inferior level (hygiene seekers), while the individuals doing non-routine work tend to be 'motivated in a superior level (motivation seekers) besides they are less conformistic, orderly and meticulous than the first ones. The results has allowed to conc1ude that, supposed, in our groups, as 1) there was significantly more 'hygiene seekers' than 'motivation seekers' among individuals doing routine work and there was significantly more 'motivation seekers' than 'hygiene seekers' among individuals doing non-routine work. 2) Individuals doing routine work tended to be significantly more motivated by safety needs in comparison with individuals doing non-routine work who tended to be significantly more motivated by self-actualization needs. 3) The conformity and the tendency to order and meticulousness appeared significantly in a higher degree among individuals doing routine work.